Strategic business planning a dynamic system for improving performance & competitive advantage - Reading, Clive (Gale virtual reference library, 2002)
Outlines a business process which should improve the performance and competitive position of any company. It enables the reader to link company purpose, business goals, strategy, performance targets and an action programme into one framework.